Durability of Humoral Immune Responses to SARS-CoV-2 in Citizens of Ariano Irpino (Campania, Italy): A Longitudinal Observational Study With an 11.5-Month Follow-Up - Coppola, Annachiara; Buonerba, Carlo; Cardinale, Davide; Lo Conte, Gabriella; Sansone, Donato; Rofrano, Giuseppe; De Vita, Sabato; Morgante, Maria; Triassi, Maria; Atripaldi, Luigi; Brambilla, Gianfranco; Sabatino, Rocco; et al. (Frontiers in Public Health, 2021)
As of April 20, 2021, SARS-CoV-2 (Severe Acute Respiratory Syndrome CoronaVirus 2), the causative agent of COVID-19 (COronaVIrus Disease 19), has infected approximately 140 million people worldwide, causing around 4 million deaths. Durability of antibody response has been documented in asymptomatic cases within a population-based study conducted in the Wuhan province with an 8-month follow-up. In the mass screening campaign based on serological testing for SARS-CoV-2 conducted in the town of Ariano Irpino (Avellino, Italy) in May, 2020, 5.7% (95% CI: 5.3-6-1) had developed anti-nucleocapsid antibodies against SARS-CoV-2 among 13’444 citizens screened. In this longitudinal study, we included a total of 422 seropositive citizens enrolled in Ariano Irpino in May, 2020 who were re-tested for anti-SARS-CoV-2 antibodies in January and/or in April 27-28, that is 8,5 and 11,5 months after being found seropositive. Median (interquartile range) age of the study cohort was 46 years (29- 59), and 47 (11.1%) participants were minors, while 217 (51,4%) participants were females. There was no evidence of re-infection in any of the subjects included. Presence of anti-nuclear antibodies (Elecysis, Roche) was reported in 95.7% and 93.7% of evaluable participants in January and April 2021. Differences were reported according to age, sex and assay employed. Our findings show that antibodies remain detectable at least 11.5 months after infection in >90% of never symptomatic cases. Duration of immunity remains to be determined.